Combining rheology and MRI: Imaging healthy and tumorous brains based on mechanical properties. Issue 3 (3rd October 2016) - Kofahl, Anna‐Lisa; Theilenberg, Sebastian; Bindl, Jakob; Ulucay, Deniz; Wild, Judith; Napiletzki, Sylvia; Schu‐Schätter, Birgit; Vohlen, Alexandra; Pintea, Bogdan; Finsterbusch, Jürgen; Hattingen, Elke; Urbach, Carsten; et al.
Abstract : Purpose: It is well known that pathological changes in tissue alter its mechanical properties. This holds also true for brain tissue. In case of the brain, however, obtaining information about these properties is hard due to the surrounding cranial bone. In this paper a novel technique to create an imaging contrast based on the aforementioned properties is presented. Methods: The method is based on an excitation of the brain induced by a short fall. The response of the brain tissue is measured using a motion sensitive MRI sequence. Results: The new method is tested by measurements on phantom material as well as on healthy volunteers. In a proof of principle experiment the capability of the approach to identify local alterations in the mechanical properties is shown by means of measurements on meningioma patients. Conclusion: The presented results show the feasibility of the novel method. Even in this early state of the proposed method, comparisons of measurements on meningioma patients with intraoperative palpation suggest that meningioma tissue responds differently to the excitation depending on their mechanical properties. Magn Reson Med 78:930–940, 2017. © 2016 International Society for Magnetic Resonance in Medicine.